Individual and average responses of sleep quality and daytime sleepiness after four weeks of strength training in adolescents - Maria Julia Lyra; Antonio Henrique Germano-Soares; Ladyodeyse da Cunha Silva Santiago; Daniel da Rocha Queiroz; Rafael Miranda Tassitano; Ana Patrícia Siqueira Tavares Falcão; Rodrigo Pinto Pedrosa; Mônica Vilela Heimer; Marcos André Moura dos Santos (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: To analyze the average and individual responses of sleep quality and daytime sleepiness in adolescents after four weeks of strength training. Methods: 19 adolescents with sleep problems recruited in the Federal Institute of Pernambuco, were subject to anthropometric evaluations as well as those for body composition assessment, a 1 repetition maximum test, the sleep parameters (Pittsburgh Sleep Quality Index-PSQI and Epworth Sleepiness Scale-ESS) and were submitted to four weeks of strength-training, performed alternately by segment, two sessions per week, according to recommendations for this population. Results: A decrease in the average PSQI score was observed (10.3±3.3 vs 8.8±4.0; p=0.006), but not in ESS (p>0.05), after intervention. The individual analyses demonstrated that ~63% of adolescents experienced reductions ≥ 3 points in the PSQI and ~58% of them experienced reductions ≥ 3 points in the measure of daytime sleepiness. The prevalence of poor sleep quality and daytime sleepiness reduced from 84.2% to 68.4% and from 52.6% to 31.6%, respectively. The comparisons of high and low responders to exercise training show that adolescents who reduced ≥3 points in the score of a least one sleep parameter presented lower weight, fat mass, and fat percentage (p<0.05). Conclusion: A short-term strength-training program is able to improve global sleep quality, but not daytime sleepiness in adolescents. Furthermore, the changes after training are highly heterogeneous. Further studies are required to better understand the effects of strength training on sleep parameters of adolescents.